(untitled) (Journal of Hama University, 2025)
The research aimed to identify the psychological and social effects of marital violence on women. To achieve the research goal, the researcher prepared a scale consisting of two sections: the first section included personal data, and the second section consisted of (26) items divided into two dimensions: psychological effects and social effects. The questionnaire was applied to a sample. It consists of (33) male and female workers at community centers during the academic year 2022-2023. The results of the research showed: a high level of the psychological and social effects of marital violence on women from the point of view of workers in community centers, according to the correction key adopted in the research. The results also showed that there were no statistically significant differences between the average scores of the sample members on the effects of violence on women due to the variable of the woman’s professional status, while the results showed that there were statistically significant differences between the average scores of the sample members on the effects of violence on women due to the variable of the woman’s educational level.